ANALISIS KEBUTUHAN LIFT GEDUNG MERAH YAYASAN MABADI’UL IHSAN BERDASARKAN SNI: 03-6573-2001 - Herni Puspitasari, Rayhan Darrel Nafari; Rahayu Pradita; Wahyu Naris Wari; Megalita Rodiyani; Wahyu Satyaning Budhi (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
The Red Building of Foundation Mabadi’ul Ihsan functioned as an educational facility for both school and university-level activities, consisting of five floors in the central area and seven floors on the sides. Currently, the building lacks a vertical transportation system such as an elevator, which is essential to support vertical mobility, especially considering the high volume of daily activity and the accessibility needs of its users. This study aims to calculate the required number and capacity of elevators based on SNI 03-6573-2001, the Indonesian national standard for planning vertical transportation systems in buildings. This standard provides technical guidelines for calculating, installing, and operating elevators to ensure safety, efficiency, and user comfort. The research methodology includes literature review, preliminary surveys, data collection, data analysis, result discussion, and the formulation of conclusions and recommendations. Through this structured approach, the study seeks to determine accurate elevator requirements tailored to the building’s capacity and usage. The final outcome is expected to serve as a practical recommendation for the building management in considering the implementation of elevators. By doing so, the overall comfort and accessibility for students, faculty, and visitors can be significantly improved, thereby enhancing the effectiveness and inclusiveness of educational activities within the facility.